Crushed by a rational stampede: Strategic share dumping and shareholder insurrections - Noe, T; Attari, M; Banerjee, S (2006)
In this paper, we develop a dynamic model of institutional share dumping surrounding control events. Uninformed institutional investors dump shares, despite trading losses, in order to manipulate share prices and trigger activism by activist "relationship" investors. Nonactivist institutional investors, who have private information regarding both firm value and the quality of their own information, are motivated to trade not only by trading profits but also by a desire to protect the value of their inventory and to disguise the quality of the information underlying their trades. Relationship investors, who use price and volume information to identify target firms, profit both from improving firm performance and from their private information about their own targeting activity. In addition to explicating recent empirical results on the relationship between institutional investor trading and corporate control events, the paper provides a number of new insights into the interaction between market microstructure and corporate governance, including predictions regarding the effect of share volume on subsequent governance activity, the relationship between the trading patterns of activist and nonactivist strategic investors, the effect of order flow on subsequent shareholder activism, and the effect of institutions' portfolio positions on the informativeness of their trading activity.